Method for preparing a catalyst for the synthesis of 1,2-dichloroethane - BOSSI; ALESSANDRO; CAVATERRA; ENRICO (1989)
A method for preparing a catalyst for the synthesis of 1,2-dichloroethane by oxychlorination of C2H4 within a fluidized bed, said catalyst containing magnesium, from 1 to 10% by weight of Cu and a carrier consisting of Al2O3, said carrier being impregnated, with an aqueous solution containing both CuCl2 and MgCl2, the amount of MgCl2 being such that the molar ratio: as defined in the text, is at least 40% higher than the molar ratio: the ratio W=X:Y being therefore >/=1.40 and the surface area of the carrier ranging between 80 and 170 sq.m/g.